DIGITAL FASHION DAN IDENTITAS REMAJA: PERAN DUKUNGAN SOSIAL DAN TANTANGAN PERBANDINGAN SOSIAL - Fadilah, Nur; Arifin, Ibrahim; Wahyuni, Sri (DISCOURSE: Indonesian Journal of Social Studies and Education, 2024)
Positive self-esteem among young people, combined with social support through social media interactions, provides a significant emotional boost. However, the risk of social comparison remains a challenge that needs to be addressed. This article discusses that adolescents who are exposed to fashion content that emphasizes certain beauty standards tend to have a negative body image and lack self-confidence. In addition, actively participating in digital fashion trends is also an important factor in increasing adolescents' self-confidence. This research is a qualitative research through an interview process. The results show that digital fashion content increases teens' self-awareness, inspiring them to try new styles. However, it also pressures them to conform to unrealistic beauty standards, thus affecting their self-image and confidence. Active participation in digital fashion trends and digital fashion communities boosts teens' self-confidence. Social validation and relationships with like-minded individuals boost self-esteem. Online groups and forums provide emotional support, helping teens find their unique style.